THE CONNECTION BETWEEN FOOD SAFETY, PUBLIC HEALTH, AND ANIMAL WELFARE - Davis, Lauren (My University, 2023)
This report summarizes the online and in-person field experiences during the period from June of 2022 until January of 2023. The author interacted with various mentors from the United States and Europe to learn about food safety, public health, and animal welfare. Food safety and animal welfare standards and regulations, both national and international, are discussed as well as the connections of each to public health. The MPH competencies and the Food Safety and Biosecurity emphasis learning competencies were achieved through the field experience and coursework. The products created during the field experience include a presentation on the relationships between animal welfare, food safety and public health; a standardized Bison Harvest Plant audit tool; a blog article discussing food safety, animal welfare, and public health from a One Health perspective; and a One Health Newsletter reflection article on the 2022 International Mobility of Veterinary Students (iMOVES) hybrid learning experience.
Keywords: food safety; animal welfare; Public Health; Connections; One Health